Justification of the efficacy of antibacterial therapy for the treatment of chronic endometritis - N. I. Tapilskaya; S. A. Karpeyev; S. N. Gaidukov (Vestnik Dermatologii i Venerologii, 2017)
A review of studies on chronic endometritis enables the authors to conclude that bacterially contaminated endometrium is the reason causing reduced fertility in case of confirmed subclinical inflammation. Chronic subclinical inflammation of the endometrium is often associated with genital endometriosis, which apparently leads to abnormal uterine bleedings. The identification of a microbial agent in case of endometritis in the routine outpatient practice is not mandatory because global experience including high-level evidence-based studies confirms the expediency of an empirical therapy based on minimum clinical criteria; otherwise, there may be irreversible consequences for the reproductive system. A preventive antibacterial therapy during the pre-conception period in infertile patients suffering from recurrent miscarriages is an efficient method to prevent reproductive losses.